THE INFLUENCE OF THE WORK ENVIRONMENT, ORGANIZATIONAL COMMITMENT, COMPENSATION, AND COMMUNICATION ON THE PERFORMANCE OF BATAM CITY GOVERNMENT EMPLOYEES - Sri Idayu; Mira Yona; Denny Ammari Ramadhan; Ratu Jovita br Simbolon (Jurnal Apresiasi Ekonomi, 2026)
This study aims to analyze the influence of work environment, organizational commitment, compensation, and communication on employee performance at the Library and Archives Office of Batam City Government. A quantitative approach was used, employing a total sampling method involving all 40 employees as respondents. Data were collected through questionnaires and analyzed using SPSS version 26. The validity test results showed that all questionnaire items had a correlation coefficient (r-count) greater than 0.312, indicating that all items were valid. The reliability test revealed Cronbach's Alpha values above 0.7 for all variables, with the highest value for the communication variable (0.887), indicating high reliability. The results of multiple linear regression analysis showed that all four independent variables significantly affected employee performance with significance levels as follows: work environment (p=0.015), organizational commitment (p=0.000), compensation (p=0.000), and communication (p=0.000). The R Square value of 0.715 indicates that 71.5% of the variation in employee performance can be explained by the independent variables, while the remaining 28.5% is influenced by other factors outside the model. The F-test also showed a significant simultaneous influence of the four variables on performance (F = 158.648 > F table = 3.09; p = 0.000). These findings emphasize that efforts to improve employee performance must be carried out holistically through improvements in the work environment, strengthening of organizational commitment, provision of fair compensation, and implementation of effective communication within the organization. Keywords : Work Environment, Organizational Commitment, Compensation, Communication, Employee Performance